A Systematic Literature Review: Developing a Transformative Leadership Model to Foster Innovative School Climate and Student Learning Independence - Muhammad Aridi (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to develop a theoretically grounded transformative leadership model that fosters an innovative school climate to enhance student learning independence. A Systematic Literature Review (SLR) was conducted following PRISMA guidelines, analyzing 15 peer-reviewed articles from Scopus, Web of Science, and ERIC. Thematic synthesis revealed that transformative leadership is characterized by visionary communication and intellectual stimulation as dominant dimensions. The synthesis further demonstrates that innovative school climate - defined by psychological safety, collaboration, and risk-taking - mediates the relationship between leadership practices and student learning independence. The proposed model links transformative leadership (input), innovative school climate (process), and student learning independence (outcome), extending path-goal theory by illustrating cascading effects from leaders to teachers to students. This study contributes a comprehensive framework for school principals and policymakers seeking to cultivate student autonomy through leadership-driven climate change. Limitations include reliance on existing literature and the need for future empirical validation of the proposed model.